KAJIAN TEMATIK KONSEP MAKANAN BERASASKAN TUMBUHAN DALAM AYAT 99 SURAH AL-AN‘AM BERDASARKAN KITAB TAFSĪR MAFĀTĪHUL GHAYB: THE CONCEPT OF PLANT-BASED FOOD IN VERSE 99 OF SURAH AL-AN‘AM: A THEMATIC STUDY OF TAFSĪR MAFĀTĪHUL GHAYB - Nurul Saadah Mohammad Zaini; Robiatul Adawiyah Mohd (Maʿālim al-Qurʾān wa al-Sunnah, 2022)
Humans require food to survive. Plants are one of the sources of human food. The concept of plants based on the Quran is explored in various interesting themes, but there is still room for research on this topic, such as the study about the concept of plant-based food based on Imam Al-Razi in Tafsīr Mafātīhul Ghayb. This tafsīr was chosen because it broadens the naqli and aqli aspects that can be used in modern scientific studies, particularly in the fields of nutritional science and medicine. Thus, based on Tafsīr Mafātīhul Ghayb, this study will examine verse 99 of surah al-An‘am. Tafsīr Mafātīhul Ghayb is regarded as a useful reference in the study of plant sources in the food according to the Quran. This qualitative study used the content analysis method and thematic analysis on surah al-An‘am verse 99. According to the study’s findings, this verse describes the concept of plant-based food by incorporating six themes: plants come from water, green elements of plants, the hierarchy of plant-based food, plant category, fruit ripening phase, and Allah SWT as the Creator of plants.